2016
DOI: 10.1542/hpeds.2015-0277
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fail Points for Discharging Pediatric Patients With New Tracheostomy and Ventilator

Abstract: As a result of this initial investigation, application to the state agency and training for caregivers have been initiated sooner, when a tracheostomy is first placed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 10 publications
(11 reference statements)
0
42
0
2
Order By: Relevance
“…Through an initial investigation of the discharge process of pediatric patients with ventilators and tracheostomies in the Pulmonary Habilitation Program, Sobotka and colleagues have shown that approval of public funding and staffing of home nursing present two major barriers to the discharge process. 30 Collaboration among state agencies, nursing agencies, and hospital teams and the use of transitional care facilities may present opportunities for streamlining the discharge process and ultimately reducing readmissions. Creating comprehensive medical homes for medically complex children as well as integrated outpatient programs for children with tracheostomy may provide access to care outside of the hospital and reduce readmissions by providing regular follow-up care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through an initial investigation of the discharge process of pediatric patients with ventilators and tracheostomies in the Pulmonary Habilitation Program, Sobotka and colleagues have shown that approval of public funding and staffing of home nursing present two major barriers to the discharge process. 30 Collaboration among state agencies, nursing agencies, and hospital teams and the use of transitional care facilities may present opportunities for streamlining the discharge process and ultimately reducing readmissions. Creating comprehensive medical homes for medically complex children as well as integrated outpatient programs for children with tracheostomy may provide access to care outside of the hospital and reduce readmissions by providing regular follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…Creating comprehensive medical homes for medically complex children as well as integrated outpatient programs for children with tracheostomy may provide access to care outside of the hospital and reduce readmissions by providing regular follow-up care. 30 Future studies should investigate discharge procedures and follow-up care received by patients to investigate variations in patient and parent education on topics that could contribute to increased readmissions due to infections. Finally, our data may be used to risk stratify patients that may benefit from targeted intervention or improved care coordination to minimize readmission risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reimbursement rates must support ongoing education of home nursing staff in areas of safety and technology . An added benefit to higher overall reimbursement rates and the availability of highly competent home care staff is the potential reduction in inpatient hospital days …”
Section: Discussionmentioning
confidence: 99%
“…24 An added benefit to higher overall reimbursement rates and the availability of highly competent home care staff is the potential reduction in inpatient hospital days. 25 There are many variables which affect the results of this study. In any pre/posttest design there is the possibility of participants "learning" the test and cuing into information which results in significant improvements in post test score.…”
Section: Factors Predicting Higher Scoresmentioning
confidence: 99%
“…When hospitalized, children with HMV assistance present with multiple comorbidities which require complex tertiary care . They have long hospitalizations, frequent readmissions, multiple providers involved in their care, high inpatient resource utilization, and challenging care coordination demands . Examples of outpatient needs include private duty nursing, durable medical equipment, primary care and subspecialty appointment coordination, and therapy and special education services.…”
Section: Introductionmentioning
confidence: 99%